DETERMINATION OF SUBJECTS’ SIGNIFICANCE RATE AND OPTIMAL INFORMATION CONTROL IN SOCIAL NETWORKS - Guseynov, Sharif; Berežnojs, Aleksandrs; Aleksejeva, Jekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This paper examines social networks, where each agent is characterized by some dynamic parameters, the dynamics of which is resulting from the influence of other agents having their own objective functions and limiting factors, as well as from control/governing body with its own objective function. In this paper, referring to the type of social networks described above, the following two interrelated problems are investigated: the problem of determining the degree of information influence on social networks; the problem of finding optimal control in social networks.